Human Rights and Climate Change : A Review of the International Legal Dimensions - McInerney-Lankford, Siobhan; Darrow, Mac; Rajamani, Lavanya (World Bank, 2012)
The study includes a conceptual overview of the link between climate impacts and human rights, focused on the relevant legal obligations underpinning the international law frameworks governing both human rights and climate change. As such it makes a significant contribution to the global debate on climate change and human rights by offering a comprehensive analysis of the international legal dimensions of this intersection. The study helps advance an understanding of what is meant, in legal and policy terms, by the human rights impacts of climate change through examples of specific substantive rights. It gives a legal and theoretic perspective on the connection between human rights and climate change along three dimensions: first, human rights may affect the enjoyment of human rights. Second, measures to address human rights may impact the realization of rights and third, that human rights have potential relevance to policy and operational responses to climate change, and may promote resilience to climate change, including in developing countries in a way that may help sustainable development. This study effectively consolidates knowledge from the fields of international human rights law, international law governing climate change and international environmental law, building on the existing work of the United Nation (UN) office of the high commissioner on human rights, the UN human rights council and the international council on human rights policy. Although it maintains a legal focus, the study has benefited from the input of a host of international experts from other disciplines as well.